42.0k views
4 votes
Type the correct answer in the box. Use numerals instead of words.What is the solution to this equation?3(n – 9) – 2(n +4) = 6nn =

User Edgard
by
6.0k points

1 Answer

5 votes

Given:

The given equation is,


3(n-9)-2(n+4)=6n

Required:

The solution to this equation.

Answer:

Let us find the solution to the given equation.


\begin{gathered} 3(n-9)-2(n+4)=6n \\ \Rightarrow3n-27-2n-8-6n=0 \\ \Rightarrow-5n-35=0 \\ \Rightarrow-5n=35 \\ \Rightarrow n=-(35)/(5) \\ \Rightarrow n=-7 \end{gathered}

Final Answer:

The solution to the given equation is,


n=-7

User Alexandre Ouicher
by
6.3k points